2011
DOI: 10.2134/agronj2010.0424
|View full text |Cite
|
Sign up to set email alerts
|

Yield, Protein, and Remobilization of Water Soluble Carbohydrate and Nitrogen of Three Spring Wheat Cultivars as Influenced by Nitrogen Input

Abstract: Plant breeders have attempted to use extended green leaf duration (EGLD) traits for spring wheat (Triticum aestivum L.) yield improvement in Montana. The objective of this study was to investigate the yield, protein, harvest index (HI), remobilization of water‐soluble carbohydrate (WSCRM) and nitrogen (NRM), N uptake, nitrogen harvest index (NHI) and nitrogen recovery in grains (NRG) of two spring wheat cultivars with EGLD (Vida and Reeder) and one without the traits (Outlook) as influenced by N input rates at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
18
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 58 publications
7
18
0
1
Order By: Relevance
“…The positive yield response as a result of the single standard NAM in Exp. Biomass production generally increases and HI generally decreases with greater N availability in perennial ryegrass as was observed in our study and is often observed in small grain crops (Table 3 and 5) (Chen et al, 2011;Cookson et al, 2000). Thousand seed weight (TSW) as affected by the interaction between growth regulator program (GRP) and N application method (NAM).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The positive yield response as a result of the single standard NAM in Exp. Biomass production generally increases and HI generally decreases with greater N availability in perennial ryegrass as was observed in our study and is often observed in small grain crops (Table 3 and 5) (Chen et al, 2011;Cookson et al, 2000). Thousand seed weight (TSW) as affected by the interaction between growth regulator program (GRP) and N application method (NAM).…”
Section: Discussionsupporting
confidence: 77%
“…2 2009 and 2010 final RCI readings, respectively) suggesting that early harvest season N availability was less critical for obtaining a seed yield response and that split N applications may be more appropriate when a fall N application has been made. Biomass production generally increases and HI generally decreases with greater N availability in perennial ryegrass as was observed in our study and is often observed in small grain crops (Table 3 and 5) (Chen et al, 2011;Cookson et al, 2000). The effect of NAM on biomass and HI in our study may have been caused by differences in N availability during periods of vigorous vegetative growth however the effects were drastically different in each year, probably due to weather, plant growth patterns, and timing of N application.…”
Section: Nitrogen Application Methodssupporting
confidence: 81%
“…Chen et al 2011;Chen et al 2010;Spano et al 2003; and review by Gregersen et al 2013). In some cases, this is accompanied by reductions in nitrogen remobilisation efficiency (Chen et al 2010(Chen et al , 2011Spano et al 2003) and low harvest index (Gong et al 2005). These findings illustrate some of the constraints imposed by the growth environment that can limit the productivity of a crop, making it difficult in practice to exploit any potential benefits offered by delayed senescence.…”
Section: Functional Stay-green Plantsmentioning
confidence: 96%
“…There is however an increasing number of reports demonstrating that cultivars with delayed senescence ('staygreen' phenotypes) characteristics, particularly in wheat, are functional stay-green plants having increased yields (e.g. Chen et al 2011;Chen et al 2010;Spano et al 2003; and review by Gregersen et al 2013). In some cases, this is accompanied by reductions in nitrogen remobilisation efficiency (Chen et al 2010(Chen et al , 2011Spano et al 2003) and low harvest index (Gong et al 2005).…”
Section: Functional Stay-green Plantsmentioning
confidence: 99%
See 1 more Smart Citation